Cell Tracking for Organoids: Lessons From Developmental Biology - Betjes, Max A.; Zheng, Xuan; Kok, Rutger N. U.; van Zon, Jeroen S.; Tans, Sander J. (Frontiers in Cell and Developmental Biology, 2021)
Organoids have emerged as powerful model systems to study organ development and regeneration at the cellular level. Recently developed microscopy techniques that track individual cells through space and time hold great promise to elucidate the organizational principles of organs and organoids. Applied extensively in the past decade to embryo development and 2D cell cultures, cell tracking can reveal the cellular lineage trees, proliferation rates, and their spatial distributions, while fluorescent markers indicate differentiation events and other cellular processes. Here, we review a number of recent studies that exemplify the power of this approach, and illustrate its potential to organoid research. We will discuss promising future routes, and the key technical challenges that need to be overcome to apply cell tracking techniques to organoid biology.